Exploring Untapped GIS Application Possibilities for the Integration of Environment-Inclined Pedagogy in Geography Education: A South African Case Study - Ndivhuwo Precious Mudau; Headman Hebe (Universitas Negeri Gorontalo, 2025)
The ubiquity of perennially evolving environmental challenges threatening the sustainability of the biophysical environment, the lifeblood of Planet Earth, require ceaseless innovative approaches to offset their calamitously impact. Over the years, environmental education (EE) has been useful in empowering learners, globally, with strategies to effectively address environmental issues. Geography is one of the school subjects that accommodate the infusion of EE in pedagogy. Significantly, the Geographical Information Systems (GIS) is one of the tools that can be used meaningfully to enable environment-inclined pedagogy in geography education. This interpretivist-qualitative study evaluates the application of GIS in the teaching of Grades 10 to 12 geography curriculum in South Africa and its potential for supporting the integration of EE in the subject. The content analysis of the Curriculum and Assessment Policy Statement (CAPS) that guides pedagogy in Grades 10 to 12 and Grade 12 November 2024 geography examination papers was used as the only research strategy while the inductive and deductive modes of reasoning aided the process of document content analysis. The findings of the study suggest that CAPS contains various themes that can be used to infuse EE using GIS in geography education. However, despite its usefulness and potential enabler of environment-inclined pedagogy in geography pedagogy, GIS is not meaningfully accommodated in geography education. The study recommends an expansion of the GIS content in the Grade 10 to 12 geography curriculum, provision of guidance to teachers on how to infuse EE using GIS and scaling up of GIS tools South African schools.